Integral Integral 4

Calculus Level pending

0 1 log 2 ( 1 x 2 + x + 1 x + 1 ) d x = a + b G + π 2 c d f log ( 2 ) + g log 2 ( 2 ) h + π ( k log ( 2 ) m j ) \int_0^1 \log ^2\left(\frac{1}{x^2}+x+\frac{1}{x}+1\right) \, dx=a+b G+\frac{\pi ^2 c}{d}-f \log (2)+\frac{g \log ^2(2)}{h}+\pi \left(\frac{k \log (2)}{m}-j\right)

where G G is Catalan's constant , and a , b , c , d , f , g , h , j , k , m a,b,c,d,f,g,h,j,k,m are positive integers. Submit a + b + c + d + f + g + h + j + k + m a+b+c+d+f+g+h+j+k+m .


The answer is 66.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

We begin by factorising

1 + 1 x + x + 1 x 2 = ( 1 + x ) ( 1 + 1 x 2 ) \displaystyle 1+\frac { 1 }{ x } +x+\frac { 1 }{ { x }^{ 2 } } =\left( 1+x \right) \left( 1+\frac { 1 }{ { x }^{ 2 } } \right)

0 1 ln 2 ( 1 + x + 1 x + 1 x 2 ) d x = 0 1 ( ln 2 ( 1 + x ) + 2 ln ( 1 + x ) ln ( 1 + 1 x 2 ) + ln 2 ( 1 + 1 x 2 ) ) d x \displaystyle \int _{ 0 }^{ 1 }{ \ln { ^{ 2 } } { (1+x+\frac { 1 }{ x } +\frac { 1 }{ { x }^{ 2 } } ) }dx } =\int _{ 0 }^{ 1 }{ \left( \ln^{2}(1+x)+2\ln(1+x)\ln(1+\frac{1}{x^{2}})+\ln^{2}(1+\frac{1}{x^{2}}) \right) dx }

Now, we integrate each term separately

0 1 ( ln 2 ( 1 + x ) ) d x = x ln 2 ( 1 + x ) 2 0 1 2 ln ( 1 + x ) 1 + x d x = ln 2 2 2 [ 0 1 ( ln 1 + x ln 1 + x 1 + x ) ] = 2 ( ln 2 1 ) 2 \displaystyle \int _{ 0 }^{ 1 }{ \left( \ln { ^{ 2 } } (1+x) \right) dx } =x\ln^{2}(1+x)-2\int^{1}_{0}{\dfrac{2\ln(1+x)}{1+x} dx }=\ln^{2}{2}-2 \left[ \int^{1}_{0}{(\ln{1+x}-\dfrac{\ln{1+x}}{1+x})} \right ]=2(\ln{2}-1)^{2}

0 1 ( ln 2 ( 1 + 1 x 2 ) ) d x = x ln 2 ( 1 + 1 x 2 ) + 4 0 1 ln 1 + x 2 2 ln x 1 + x 2 d x \displaystyle \int _{ 0 }^{ 1 }{ \left( \ln { ^{ 2 } } (1+\dfrac{ 1 }{ x^{ 2 } }) \right) dx } =x\ln { ^{ 2 } } (1+\frac{ 1 }{ x^{ 2 } })+4\int _{ 0 }^{ 1 }{ \frac { \ln{1+x^{2}}-2\ln{x} }{ 1+x^{2} } dx }

Now

0 1 ln 1 + x 2 2 ln x 1 + x 2 d x = 1 ln 1 + x 2 1 + x 2 d x \displaystyle \int _{ 0 }^{ 1 }{ \frac { \ln { 1+x^{ 2 } } -2\ln { x } }{ 1+x^{ 2 } } dx } =\int _{ 1 }^{ \infty }{ \frac { \ln { 1+x^{ 2 } } }{ 1+x^{ 2 } } dx }

So,

0 ln 1 + x 2 1 + x 2 d x + 0 1 2 ln x 1 + x 2 d x = 2 1 ln 1 + x 2 1 + x 2 d x \displaystyle \int _{ 0 }^{ \infty }{ \frac { \ln { 1+x^{ 2 } } }{ 1+x^{ 2 } } dx } +\int _{ 0 }^{ 1 }{ \frac { -2\ln { x } }{ 1+x^{ 2 } } dx } =2\int _{ 1 }^{ \infty }{ \frac { \ln { 1+x^{ 2 } } }{ 1+x^{ 2 } } dx }

To evaluate each term, we first let

J ( a ) = 0 ln 1 + a 2 x 2 1 + x 2 d x \displaystyle J(a)=\int _{ 0 }^{ \infty }{ \frac { \ln { 1+{ a }^{ 2 }x^{ 2 } } }{ 1+x^{ 2 } } dx }

J ( a ) = 0 2 a x 2 ( 1 + x 2 ) ( 1 + a 2 x 2 ) d x = 2 a 1 a 2 ( 0 1 ( 1 + a 2 x 2 ) d x 0 1 ( 1 + x 2 ) d x ) = π 1 + a \displaystyle J'(a)=\int _{ 0 }^{ \infty }{ \frac { { 2ax }^{ 2 } }{ (1+x^{ 2 })(1+{ a }^{ 2 }{ x }^{ 2 }) } dx } =\frac { 2a }{ 1{ -a }^{ 2 } } \left( \int _{ 0 }^{ \infty }{ \frac { 1 }{ (1+{ a }^{ 2 }{ x }^{ 2 }) } dx } -\int _{ 0 }^{ \infty }{ \frac { 1 }{ (1+x^{ 2 }) } dx } \right) =\frac { \pi }{ 1+a }

So,

J ( 1 ) = π ln 2 \displaystyle J(1)=\pi\ln{2}

0 1 ln x 1 + x 2 d x = ln x tan 1 x 0 1 tan 1 x x d x = G \displaystyle \int _{ 0 }^{ 1 }{ \frac { \ln { x } }{ 1+{ x }^{ 2 } } dx } =\ln{x}\tan^{-1}{x}-\int _{ 0 }^{ 1 }{ \frac {\tan^{-1}{x}}{ x } dx } =-G (The last can be done easily by expanding the infinite series for tan 1 x \tan^{-1}{x} )

0 1 ln 1 + x 2 2 ln x 1 + x 2 d x = π ln 2 2 + G \displaystyle \int _{ 0 }^{ 1 }{ \frac { \ln { 1+x^{ 2 } } -2\ln { x } }{ 1+x^{ 2 } } dx }=\dfrac{\pi\ln{2}}{2}+G

Now, the last one ;D

0 1 ln x ln 1 + 1 x 2 d x = x ln x ln 1 + 1 x 2 0 1 x 1 + x ln 1 + 1 x 2 d x + 2 0 1 ln 1 + x 1 + x 2 d x \displaystyle \int _{ 0 }^{ 1 }{ \ln { x } \ln { 1+\frac { 1 }{ { x }^{ 2 } } } dx } =x\ln { x } \ln { 1+\frac { 1 }{ { x }^{ 2 } } } -\int _{ 0 }^{ 1 }{ \frac { x }{ 1+x } \ln { 1+\frac { 1 }{ { x }^{ 2 } } } dx } +2\int _{ 0 }^{ 1 }{ \frac { \ln { 1+x } }{ 1+{ x }^{ 2 } } dx }

By letting

K ( a ) = 0 1 ln 1 + a x 1 + x 2 d x \displaystyle K(a)=\int _{ 0 }^{ 1 }{ \frac { \ln { 1+ax } }{ 1+{ x }^{ 2 } } dx }

We have

K ( a ) = 0 1 x ( 1 + x 2 ) ( 1 + a x ) d x = a 1 + a 2 0 1 1 + x a ( 1 + x 2 ) 1 ( 1 + a x ) d x = a 1 + a 2 ( π 4 + ln 2 2 a ln 1 + a a ) \displaystyle K'(a)=\int _{ 0 }^{ 1 }{ \frac { x }{ (1+{ x }^{ 2 })(1+ax) } dx } =\frac { a }{ 1+{ a }^{ 2 } } \int _{ 0 }^{ 1 }{ \frac { 1+\frac { x }{ a } }{ (1+{ x }^{ 2 }) } -\frac { 1 }{ (1+ax) } dx } =\frac { a }{ 1+{ a }^{ 2 } } \left( \frac { \pi }{ 4 } +\frac { \ln { 2 } }{ 2a } -\frac { \ln { 1+a } }{ a } \right)

So,

K ( 1 ) K ( 0 ) = π ln 2 4 K ( 1 ) \displaystyle K(1)-K(0)=\dfrac{\pi\ln{2}}{4}-K(1) Note that K ( 0 ) = 0 K(0)=0 Then,

0 1 ln 1 + x 1 + x 2 d x = π ln 2 8 \displaystyle \int _{ 0 }^{ 1 }{ \frac { \ln { 1+x } }{ 1+{ x }^{ 2 } } dx } =\frac { \pi \ln { 2 } }{ 8 }

0 1 ln x ln 1 + 1 x 2 d x = ln 2 2 + π ln 2 4 0 1 ( 1 1 1 + x ) ln ( 1 + x 2 ) d x + 2 0 1 ( 1 1 1 + x ) ln x d x \displaystyle \int _{ 0 }^{ 1 }{ \ln { x } \ln { 1+\frac { 1 }{ { x }^{ 2 } } } dx } =\ln^{2}{2}+\dfrac{\pi\ln{2}}{4}-\int_{0}^{1}{(1-\dfrac{1}{1+x})\ln{(1+x^{2})}dx}+2 \int_{0}^{1}{(1-\dfrac{1}{1+x})\ln{x}dx}

Now we just need to integrate the last 4 terms,( from here on I deliberately leave out the limit of integration for the sake of simplicity , therefore the limit is well known to be from 0 to 1)

ln 1 + x 2 = ln 2 2 + π 2 d x \displaystyle \int\ln{1+x^{2}}=\ln{2}-2+\dfrac{\pi}{2}dx (The integral here is easy, so, I leave it as an exercise.)

ln x d x = 1 \displaystyle \int\ln{x}dx=-1

ln x 1 + x = ln 1 + x x = π 2 12 \displaystyle \int{\dfrac{\ln{x}}{1+x}}=-\int{\dfrac{\ln{1+x}}{x}}=-\dfrac{\pi^{2}}{12} (This integral is done by expanding the series for logarithm and knowing the fact that 1 1 n 2 = π 2 6 \displaystyle \sum_{1}^{\infty}{\dfrac{1}{n^{2}}}=\dfrac{\pi^{2}}{6} )

ln 1 + x 2 1 + x d x = π 2 48 + 3 ln 2 2 4 \displaystyle \int{\dfrac{\ln{1+x^{2}}}{1+x}dx}=-\dfrac{\pi^{2}}{48}+\dfrac{3\ln^{2}{2}}{4}

The last integral can be done by lettting

L ( a ) = ln 1 + a 2 x 2 1 + x d x \displaystyle L(a)=\int{\dfrac{\ln{1+a^{2}x^{2}}}{1+x}dx}

L ( a ) = 2 a 1 + a 2 ( 1 1 + x + x 1 1 + a 2 x 2 d x ) \displaystyle L'(a)=\dfrac{2a}{1+a^{2}}(\int{\dfrac{1}{1+x}+\dfrac{x-1}{1+a^{2}x^{2}}dx}) (Recall L ( 0 ) = 0 \displaystyle L(0)=0 )

We get,

L ( 1 ) = ln 2 2 π 2 16 + ln ( 1 + x 2 ) x ( 1 + 2 ) d x = ln 2 2 π 2 16 + ln ( 1 + x 2 ) x d x x ln ( 1 + x 2 ) 1 + x 2 d x \displaystyle L(1)=\ln^{2}{2}-\dfrac{\pi^{2}}{16}+\int{\dfrac{\ln(1+x^{2})}{x(1+^{2})}dx}=\ln^{2}{2}-\dfrac{\pi^{2}}{16}+\int{\dfrac{\ln(1+x^{2})}{x}dx}-\int{\dfrac{x\ln(1+x^{2})}{1+x^{2}}dx}

L ( 1 ) = ln 2 2 π 2 16 ln 2 2 4 + π 2 24 \displaystyle L(1)=\ln^{2}{2}-\dfrac{\pi^{2}}{16}-\dfrac{\ln^{2}{2}}{4}+\dfrac{\pi^{2}}{24}

Combining all these togather

0 1 ln 2 ( 1 + x + 1 x + 1 x 2 ) d x = 2 + 4 G + 7 π 2 24 6 ln 2 + 13 ln 2 2 + π ( 5 ln 2 2 1 ) \displaystyle \int _{ 0 }^{ 1 }{ \ln { ^{ 2 } } { (1+x+\frac { 1 }{ x } +\frac { 1 }{ { x }^{ 2 } } ) }dx }=2+4G+\dfrac{7\pi^{2}}{24}-6\ln{2}+\dfrac{13\ln^{2}}{2}+\pi(\dfrac{5\ln{2}}{2}-1)

So, a + b + c + d + f + g + h + j + k + m = 66 \displaystyle a+b+c+d+f+g+h+j+k+m=\boxed{66}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...